008 TRAINING IN CARDIOLOGY: IS END OF LIFE CARE BEING ADDRESSED?. (24th May 2013) - Ismail, Y; Shorthose, K; Nightingale, A K
Abstract : Background: It is widely accepted that end of life care for non-cancer conditions has lagged behind palliative care for cancer. To equip cardiologists of the future with the necessary knowledge, skills and behaviour, end of life care has been incorporated into the 2010 Cardiology Curriculum in the UK. The purpose of this survey was to evaluate the confidence of trainees in managing end of life issues in advanced heart failure patients. Methods: An online questionnaire was distributed to all registrar-grade British Junior Cardiac Association members in the UK. Results: The main themes from 220 respondents were: Clinical Experience: ▸ 69% of trainees experience difficulties in palliating patients with advanced heart failure. ▸ Only 54% of trainees seek specialist palliative care input when experiencing problems. ▸ 73% of trainees feel that the care that they provide patients with advanced heart failure is poor or only adequate. ▸ 70% of trainees do not routinely explain the possible future need for ICD deactivation. ▸ 84% of trainees feel that patients are better off knowing their diagnosis even if it is poor, yet more than 50% of trainees do not feel equipped to discuss advanced care planning and end of life issues when seeing advanced heart failure patients in an out-patient clinic setting. Training: ▸ 45% report receiving no training in palliation of advanced heart failure symptoms. ▸ Only 29% have received any specific training in symptom palliation of advanced heart failure at ST3 level or above. ▸ Only 17% have completed an assessment to demonstrate competencies in end of life care. ▸ 57% are unhappy with current provision of training. ▸ Over 86% think that end-of-life training is important or very important within the curriculum. ▸ In particular, trainees identify 4 key areas for specialist input: symptom control, opioid titration, communication skills and the role of the palliative care team. ▸ Trainees' suggestions include more workplace-based supervision with additional regional and national training days, closer links with local hospices and specific fellowships for heart failure trainees in palliative care. Conclusions: This survey shows that despite being part of the national curriculum for training in cardiology since 2010, trainees' level of confidence in delivering end of life care in advanced heart failure and discussing prognosis in patients with an ICD is poor. Specific training in end-of-life care remains a neglected part of the curriculum; this could be rectified by joint training with palliative care and more formal assessment of these skills.